Surgeon’s narcissism, hostility, stress, bullying, meaning in life and work environment: a two-centered analysis - El Boghdady Michael; Ewalds-Kvist Beatrice Marianne (Springer, 2025)
Introduction
Disruptive physician behaviour can affect patients’ safety. If surgical trainees throughout higher education experience disruptive behaviour, impaired work-life may follow. Therefore, we aimed to study surgeons' level of narcissism (N), hostility, and stress in relation to their work environment and potential experience of bullying. We also scrutinized search for or presence of meaning in life.
Methods
General surgeons in UK National Health Service from 2 hospitals participated with 3 levels of training: junior trainees (JT), senior trainees (ST), and consultants (CONS). Participants completed 52 VAS-formed questions plus demographics. Modified questionnaires were used for assessments of ‘hostility’, ‘narcissism’, meaning in life, quality of work-life, and bullying.
Results
Altogether 33% of surgeons displayed narcissism and 22% could exhibit disruptive behaviour. By MANOVA significant differences between low, medium, and high narcissism groups were revealed in hostility (p<.01), perceived stress (p=.001), and presence of meaning in life (p<.05). Regression analyses explained hostility both by N-scale (p=.000) and ‘being bullied during training’(p=.009) but negatively by ‘presence of meaning in life’(p=.004). Surgeons’ perceived stress was explained both by N-scale (p=.000) followed by ‘seeing others bullied during training (p=.000) and negatively by ‘working extra days beyond schedule’ (p=.007). The presence of meaning in life was explained mostly by good beneficial stress (p= .000) but negatively both by ‘doing extra work beyond schedule’ (p= .016) and hostility (p= .003).
Conclusion
Surgeons may exhibit disruptive behaviour in a challenging situation. The narcissim-scale was the best predictor of hostility and perceived stress. Being bullied during surgical training predicted hostility. Seeing others being bullied during surgical training predicted stress. Beneficial stress is explained best by surgeons’ experience of the presence of meaning in life.